Wireless Network Control System for Electro Stati Precipitator in Cement Plants - Marie, Mehdi J.; Gaied, Khalaf S.; Ajel, Ahmed R. (Al-Khwarizmi Engineering Journal, 2018)
Wireless control networks (WCNs), based on distributed control systems of wireless sensor and actuator networks, integrate four technologies: control, computer network and wireless communications. Electrostatic precipitator (ESP) in cement plants reduces the emissions from rotary kiln by 99.8% approximately. It is an important thing to change the existing systems (wireline) to wireless because of dusty and hazardous environments. In this paper, we designed a wireless control system for ESP using Truetime 2 beta 6 simulator, depending on the mathematical model that have been built using identification toolbox of Matlab v7.1.1. We also study the effect ofusing wireless network on performance and stability of the closed loop control system. Simulation results of WCN for ESP show smooth operation with a little bit of perturbation between transient and steady state region.